Profit-share bidding auctions: a theoretical approach - Souza, Clara Costellini de (2015)
In this paper, we study by means of a theoretical approach the Brazilian production sharing regime for oil exploration approved in Law No 12.351. We develop a model for production sharing to capture certain aspects of the Brazilian sharing model as compulsory participation of Petrobras, asymmetric information, and the presence of strategic participants. Using numerical solutions, we discuss the bidders’ strategies and their expected gains. Furthermore, we developed a model with heterogeneous costs to study the local content rules.